C-reactive protein to albumin ratio is associated with disease activity in anti-neutrophil cytoplasmic antibody associated vasculitis - ALİBAZ ÖNER, FATMA; DİRESKENELİ, RAFİ HANER; TUĞLULAR, ZÜBEYDE SERHAN; AŞICIOĞLU, EBRU (My University, 2023)
Objective/Aim: C-reactive protein to albumin ratio (CAR) has recently been recognized as an independent prognostic marker for vasculitides. This study aims to investigate CAR and its relationship with disease activity and damage in prevalent ANCA associated vasculitis (AAV) patients. Methods: Fifty-one patients with AAV and 42 age-sex-matched healthy controls were enrolled in this crosssectional study. Birmingham vasculitis score (BVAS) was used to assess vasculitis activity and vasculitis damage index (VDI) to provide information on disease damage. Results: The median (25th-75th) age of the patients were 55 (48-61) years. CAR was significantly higher in AAV patients than controls (1.9±2.7 vs 0.7±0.4; p=0.006). The 75th percentile of BVAS was defined as high BVAS (BVAS≥5) and ROC curve analysis showed that CAR≥0.98 predicted BVAS≥5 with 70.0% sensitivity and 68.0% specificity (AUC:0.660, CI: 0.482-0.837, p=0.049). When patients with CAR≥0.98 were compared to those without, BVAS [5.0 (3.5-8.0) vs. 2.0 (0-3.25), p<0.001], BVAS≥5 [16 (64.0%) vs 4 (15.4%) patients, p:0.001], VDI [4.0 (2.0-4.0) vs. 2.0 (1.0-3.0), p=0.006], and CAR [1.32 (1.07-3.78) vs. 0.75 (0.60-0.83), p<0.001] were higher whereas albumin [3.8 (3.1-4.3) vs. 4.1 (3.9-4.4) g/dL, p=0.025] and haemoglobin [12.1 (10.4-13.4) vs. 13.0 (12.5-14.2) g/dL, p=0.008] were lower. Multivariate analysis revealed that BVAS [OR(95% CI):1.313 (1.003-1.719), p=0.047] was an independent factor associated with CAR≥0.98 in patients with AAV. Furthermore, correlation analysis showed that CAR significantly correlated with BVAS (r: 0.466, p=0.001). Conclusion: In this study, we observed that CAR was significantly associated with disease activity in AAV patients and can be used to monitor disease activity
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ROMATOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; RHEUMATOLOGY; Romatoloji; Rheumatology; ANCA-associated vasculitis; Birmingham vasculitis activity score; C-reactive protein to albumin ratio; vasculitis damage index; ANCA-associated vasculitis; Birmingham vasculitis activity score; C-reactive protein to albumin ratio; vasculitis damage index